2021
DOI: 10.1136/bmjmilitary-2020-001679
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mental ill health in UK Army personnel: an overview

Abstract: Women in the UK military are more commonly diagnosed with a mental health disorder than men, but the reasons for this difference are not fully understood. This literature review identifies the risk factors for mental ill health in military personnel before serving, during service and as a veteran. The interaction of risk factors is complex and, in some cases, may be synergistic, such as experiencing adverse events in childhood and exposure to combat. Identification of risk factors allows further research to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…First, evidence from our study indicated that the military experience of Chinese male veterans has a positive impact on the incidence of depression, which is partially different from other countries (2-7). We believe that distinct elements of military culture, such as education, alcohol, tobacco, and tolerance, may be of key importance, because these forms of military culture may affect the individuals' lives in the long-term (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, evidence from our study indicated that the military experience of Chinese male veterans has a positive impact on the incidence of depression, which is partially different from other countries (2-7). We believe that distinct elements of military culture, such as education, alcohol, tobacco, and tolerance, may be of key importance, because these forms of military culture may affect the individuals' lives in the long-term (51).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there is increasing interest in determining the risk factors that can contribute to the mental health issues of veterans because it is increasingly being accepted that risk factors play a critical role in the development of mental health issues (23). Notably, being female, having low educational attainment, having drinking and smoking habits, or not owning a suitable house is proven to be associated with a higher risk of depression among veterans (14,(24)(25)(26)(27)(28)(29). Conversely, social support, particularly from spouses, is considered a potential protective factor for veterans (30)(31)(32).…”
mentioning
confidence: 99%
“…Common mental disorders were assessed using the 7-item Generalized Anxiety Disorder Assessment (GAD-7) (38), the 9-item Patient Health Questionnaire (PHQ-9) (39), the Perceived Stress Scale (40), and 10-item Connor-Davidson Resilience Scale (CD-RISC-10) (41). Anxiety and depression were scored according to severity using the respective GAD-7 (minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19)(20)(21)) and PHQ-9 scores (minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), severe (20)(21)(22)(23)(24)(25)(26)(27)). A participant was defined as having symptoms of anxiety if they scored ≥10 on the GAD-7 (38) and depression if they scored ≥10 on the PHQ-9 (39).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of common mental disorders is up to twofold higher in British servicemen and servicewomen compared with the general population (22,23). Servicewomen are also more likely to suffer a common mental disorder than servicemen (approximately 22%–26% compared with 16%–19%) (22,24–26), with men and women having different risk factors (19). Although much research has been conducted on deployment (27–31) and some nondeployment (32) stressors, there is little evidence exploring associations with exercise behaviors and job demands, which are important in the development of the Triad/RED-S.…”
mentioning
confidence: 99%
“…Responding to a gender data gap in defence that is also evident in wider society, as described in the editorial by Greeves et al ,2 this supplement has been curated to evaluate sex differences in musculoskeletal injuries in training3 and the trained strength,4 the biomechanics of load carriage,5 the cognitive responses to load carriage,6 and the prevalence of, and risk factors for, mental ill-health 7. We also discuss unique challenges for women, including the prevalence of injury and illness on return to work following childbirth,8 and both the prevalence of hormonal contraceptive use9 and influence of hormonal contraceptive use on bone metabolism 10.…”
mentioning
confidence: 99%